2019
DOI: 10.1111/voxs.12521
|View full text |Cite
|
Sign up to set email alerts
|

Cell‐free fetalDNAand fetal blood group genotyping: non‐invasive prenatal testing

Abstract: In transfusion medicine and clinical immunology, cell-free fetal DNA (cffDNA) is analysed from maternal plasma of pregnant women to predict fetal blood groups with the purpose of (1) assessing the risk of haemolytic disease of the fetus and newborn (HDFN) in immunized women and (2) guiding targeted Rh prophylaxis in non-immunized RhD-negative women. National programmes for guiding prophylaxis are now implemented in around 6-7 European countries; assay accuracy is very high, with sensitivities of 99Á9%. Sensiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 58 publications
0
8
2
Order By: Relevance
“…However, the specificity of an assay based on replicate testing of RHD exon 10 with 95.2% was lower than in the previous studies [32]. In our performance evaluation study, the sensitivity of 99.93% and specificity of 99.61% were as high as sensitivities and specificities determined in the second trimester with largescale screening studies [14,21,29,33]. Notably, our single false-negative result was observed at the beginning of the second trimester.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…However, the specificity of an assay based on replicate testing of RHD exon 10 with 95.2% was lower than in the previous studies [32]. In our performance evaluation study, the sensitivity of 99.93% and specificity of 99.61% were as high as sensitivities and specificities determined in the second trimester with largescale screening studies [14,21,29,33]. Notably, our single false-negative result was observed at the beginning of the second trimester.…”
Section: Discussioncontrasting
confidence: 52%
“…Since the feasibility of targeted antenatal RAADP based on the result from a NIPT for the prediction of the fetal RhD status has been proposed by Dennis Lo's group and a Dutch group in 1998 it took about 12 years until the first nationwide program for targeted RAADP was implemented in Denmark [11][12][13]. Until today many validation studies have been published and extensively reviewed which revealed an excellent diagnostic accuracy of NIPT for RhD [14][15][16][17][18][19][20][21]. It has to be stressed in the given context that only false-negative NIPT RhD results may have relevant consequences (i.e., increased risk for anti-D alloimmunisation).…”
Section: Introductionmentioning
confidence: 99%
“…However, the speci city of an assay based on replicate testing of RHD exon 10 with 95.2% was lower than in the previous studies [32]. In our performance evaluation study the sensitivity of 99.93% and speci city of 99.61% were as high as sensitivities and speci cities determined in the second trimester with large-scale screening studies [14,21,29,33]. Notably, our single false negative result was observed at the beginning of the second trimester.…”
Section: Discussioncontrasting
confidence: 48%
“…Since the feasibility of targeted antenatal RAADP based on the result from a NIPT for the prediction of the fetal RhD status has been proposed by Dennis Lo's group and a Dutch group in 1998 it took about 12 years until the rst nationwide program for targeted RAADP was implemented in Denmark [11][12][13]. Until today many validation studies have been published and extensively reviewed which revealed an excellent diagnostic accuracy of NIPT for RhD [14][15][16][17][18][19][20][21]. It has to be stressed in the given context that only false negative NIPT RhD results may have relevant consequences (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Non‐invasive testing of cell‐free DNA (cfDNA) has become highly relevant in clinical medicine, with clinical applications in prenatal diagnosis [1,2], cancer [3] and transplantation [4]. In transfusion medicine and clinical immunology, non‐invasive testing of cell‐free fetal DNA (cffDNA) is used to predict fetal blood groups [5], including clinical applications for fetal RHD genotyping [6,7] and genotyping of fetal non‐RhD antigens [8‐10], to assist in pregnancy care where blood group incompatibility may have clinical consequences [11].…”
Section: Introductionmentioning
confidence: 99%